Aggression, Social Interactions, and Reproduction in Orphaned (Bombus impatiens) Workers: Defining Dominance - Sibbald, Emily (Université d'Ottawa / University of Ottawa, 2013)
At certain stages of a bumblebee colony life cycle workers lay eggs. Not all workers reproduce, however, since many continue to forage and care for the nest. This leads to questions regarding what differentiates a reproductive worker from a non-reproductive one. It is hypothesized that a form of reproductive competition takes place, where the most behaviourally dominant worker becomes reproductively dominant. The behaviour of orphaned Bombus impatiens pairs was recorded and aggression, social interactions, egg-laying, and ovarian development were identified. Experiment 1 examined the association between aggression and egg-laying. Contrary to the hypothesis, the most aggressive worker did not lay more eggs. When the ovarian development of workers was manipulated and two workers with developed ovaries were paired (Experiment 3), they were more aggressive than pairs with discouraged ovarian development. This provides support for the supposition that aggression and reproduction are related, however, it is only partial support as worker pairs with encouraged ovarian development did not lay more eggs. Since aggression is believed to be only one part of behavioural dominance, Experiment 2 studied the association between social interactions and aggression and reproduction. Results showed that when two socially active bees were paired they were more aggressive than pairs including one or two socially inactive bumblebees. No significant difference in ovarian development between socially active pairs and socially inactive pairs was found. Brood presence was also predicted to affect reproductive control. Experiment 1 found egg-laying and aggression were more likely to co-occur in the absence of brood. Results from Experiment 2 supplemented the first experiment since the absence of brood increased rates of aggression and ovarian development in pairs. Whereas the results confirm aggression has a role in worker reproduction the findings also reveal that behavioural dominance does not equate to reproductive dominance under all conditions. The primary contributions of this thesis were the development of a method to distinguish behavioural dominance from reproductive dominance and determining their relationship under different environments (brood presence) and experimental manipulations (ovarian development). These contributions further define dominance in Bombus impatiens.
Keywords: Bumblebee; Bombus impatiens; Aggression; Social Interactions; Eusocial insect; Reproduction; Oviposition; Ovarian development; Orphaned; Reproductive competition; Queen-less workers; Dominance